Face-to-face Training is the Preferred Modality of Professional Continuing Education for Librarians of All Ages, but More Evidence is Needed. A Review of: Lynn, V. A., Bose, A., & Boehmer, S. J. (2010). Librarian instruction-delivery modality preferences for professional continuing education. Journal of the Medical Library Association, 98(1), 57-64. - Kathryn Oxborrow (Evidence Based Library and Information Practice, 2011)
Objective – To establish the preferred modality for professional continuing education (CE) among members of three library associations. The primary hypothesis was that face-to-face training is the preferred modality, and the secondary hypothesis was that younger librarians are more likely to favour online or blended training modalities. In addition, the authors sought to investigate which factors influence participants’ decisions to take up training. Design – Online questionnaire. Setting – Three library associations based in the United States of America. These were the American Library Association (ALA), the Special Libraries Association (SLA), and the Medical Library Association (MLA). Subjects – A random sample of 328 members of the ALA (86 participants), SLA (63 participants), and MLA (291 participants). Some participants were members of more than one association. Methods – Participants were recruited to complete an online survey via direct e-mail contact (MLA), messages on email discussion lists (SLA) and social networks (ALA). The survey asked about participants’ experience of, and preference for, five different training modalities for CE. These were: face-to-face (classroom instruction), web-based synchronous (with real-time participant-instructor interaction), web-based asynchronous (with instructor involvement, but not in real time), blended (a combination of different modalities), and webcasts (live online presentations with limited participant-instructor interaction). Participants were then asked to rank factors which would influence their decision to undertake CE courses. The factors were cost, opportunity to socialize/network, time away from work, learning at their own pace, and having immediate access to either the class instructor or other participants. Participants were also given space to comment on both CE modalities and influencing factors. Main Results – There was a statistically significant preference for face-to-face instruction in this sample, being preferred by at least 73.1% of participants in all age ranges. Younger librarians did not display a preference for online or blended training modalities. There was a significant difference in second preference between ALA and MLA members, who both preferred Web based asynchronous training, and SLA members, who preferred the web-based synchronous format. Participants’ preferences for all modalities apart from face to face were significantly different depending on whether or not they had experienced the particular modality. Cost was ranked as the most influential factor in the decision to undertake CE by members of all three library associations (significant at P<0.001). The second most important factor was immediate access to the class instructor. This was also significantly higher than the other factors, which did not differ significantly between one another. Participants raised other issues such as the importance of the location of face to face training or hosted webcasts, and the likelihood of self paced training being put aside in favour of everyday work. Conclusion – The results confirm the hypothesis that face to face is the preferred training modality for this sample of members of the ALA, MLA and SLA. However, the secondary hypothesis, that younger librarians are more likely to prefer online or blended training methods was disproved in this sample. Since this is the case, and there is a strong influence of cost on the uptake of CE courses, the authors suggest that providers of CE should consider these results when planning training to suit the needs of their members.